External quality assessment for CD4 + T-lymphocyte count test: Performance of the Brazilian public health laboratories network. (May 2018) - Gaspar, Pâmela Cristina; Wohlke, Bruna Lovizutto Protti; Brunialti, Milena Karina Coló; Pires, Ana Flávia; Kohiyama, Igor Massaki; Salomão, Reinaldo; Alonso Neto, José Boullosa; Júnior, Orlando da Costa Ferreira; Franchini, Miriam; Bazzo, Maria Luiza; Benzaken, Adele Schwartz
Abstract : Abstract: The National Network for CD4+ T-lymphocyte counting of Brazil comprises 93 laboratories. This study reports the laboratory performances achieved in external quality assessment (EQA) rounds provides by Ministry of Health to evaluate the quality of the kits used and the performance of test by the technicians. Ten EQA rounds were analyzed according the EQA criteria aimed to evaluate individual laboratory performance on the basis of the accuracy of their results compared to the general mean obtained by all participating laboratories and the reproducibility of the results obtained between 2 samples from the same donor. The percentage of approved and failed laboratories in the EQAs tends to follow a uniform pattern. Since 2011, approval has remained above 80% and the failure rate has never exceeded 15%. EQA is very important to evaluate the performance of the laboratories, to identify monitor, and to resolve errors as quickly as possible.